Strategi Meningkatkan Keterampilan Pemecahan Masalah Menggunakan E-Worksheet dalam Pembelajaran IPA - Siswanto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study aims to describe the strategy of using e-worksheets to improve students' problem-solving skills in science learning at the junior high school level. The background of the study is based on the needs of 21st-century learning that requires students to master critical thinking, collaboration, and problem-solving skills. The research method uses a one-group pre-test post-test design. The research instrument used is a problem-solving test. The results showed that there was a significant difference between problem-solving skills before and after learning using e-worksheets (p 0.001), and students' problem-solving skills increased in the moderate category (n-gain score: 0.36). E-worksheets were proven to strengthen exploration activities, guide step-by-step thinking processes, and provide feedback. These findings indicate that e-worksheets can be an effective alternative learning media to improve the quality of science learning.